Working with Socially Maladjusted Youths and Children With Developmental Disorders. Predictors and Correlations of Health Among Personnel in Youth Centres - Szrajda, Justyna; Sygit-Kowalkowska, Ewa; Weber-Rajek, Magdalena; Tudorowska, Malwina; Ziółkowski, Marcin; Borkowska, Alina (Journal of Education Culture and Society, 2019)
AbstractBackgroundRepresentatives of helping professions who are working with socially maladjusted youths and children with developmental disorders are particularly exposed to occupational stress. The aim of the study was to evaluate mental and physical well-being, as well as their correlates and predictors in a group of employees working at youth educational centres and sociotherapy centres.Materials and MethodsA total of 96 employees working at youth educational centres and sociotherapy centres took part in the study. The following psychometric tools were used: the Psychosocial Working Conditions Questionnaire, the Mini-COPE, the LOT-R, and the GSES.ResultsThe results obtained indicate that people working in helping professions experience mental and physical health problems. Only 3% of the subjects declared they sleep all night. Over 40% and over 35% of the subjects estimate they suffer from low mood and irritation episodes, respectively, rather frequently or continually. Subjects with poorer mental health are more likely to use Helplessness, Avoidance behaviours, or Turning to religion to cope with stress. The strongest predictor of mental well-being is the sense of self-efficacy. Whereas, the strongest predictor of physical well-being is the ability to cope with stress by giving into the feeling of Helplessness. ConclusionsThe study demonstrated poor mental and physical well-being of the subjects. A statistically significant correlation was found between sex and the level of mental and physical health. Employees working at youth educational centres and sociotherapy centres with better mental and physical well-being had a stronger sense of self-efficacy and a higher level of life optimism.